Dependencia al teléfono móvil y rendimiento académico en estudiantes, Facultad de Enfermería Universidad Nacional de la Amazonía Peruana Iquitos 2025 - Pinedo Torres, Franck Antony (2025)
The objective of this study was to determine the relationship between mobile phone dependence and academic performance among students of the Faculty of Nursing at the National University of the Peruvian Amazon, Iquitos, in 2025. A quantitative method was used with a non-experimental, descriptive, correlational, and cross-sectional design. The population consisted of 280 students from the first to fourth levels of studies, and the sample consisted of 162 students (first level: 46; second level: 38; third level: 37; and fourth level: 41). The techniques applied were a survey and documentary review, using the Mobile Phone Dependence Test (MDT) and the academic performance record form as instruments. The data were processed using SPSS version 26 statistical software, applying descriptive statistics for univariate analysis and inferential statistics for bivariate analysis, using the nonparametric Kendall's Tau-b test, with a significance level of α < 0.05. According to the results, 51.9% of students presented medium mobile phone dependence, 42.6% low dependence, and 5.6% high dependence. Regarding academic performance, 77.2% of students showed good performance, 21.6% average, and 1.2% very good. In conclusion, a statistically significant and inverse relationship was found between mobile phone dependence and academic performance (p = 0.018; Tau-b = -0.139), indicating that less mobile phone dependence may contribute to higher academic performance.